Burial customs and the pollution of death in ancient Rome: procedures and paradoxes - Francois P. Retief; Louise Cilliers (Acta Theologica)
The Roman attitude towards the dead in the period spanning the end of the Republic and the high point of the Empire was determined mainly by religious views on the (im)mortality of the soul and the concept of the “pollution of death”. Contamination through contact with the dead was thought to affect interpersonal relationships, interfere with official duties and prevent contact with the gods. However, considerations of hygiene relating to possible physical contamination also played a role. In this study the traditions relating to the correct preparation of the body and the subsequent funerary procedures leading up to inhumation or incineration are reviewed and the influence of social status is considered. Obvious paradoxes in the Roman attitude towards the dead are discussed, e.g. the contrast between the respect for the recently departed on the one hand, and the condoning of brutal executions and public blood sports on the other. These paradoxes can largely be explained as reflecting the very practical policies of legislators and priests for whom considerations of hygiene were a higher priority than cultural/religious views.